A case of ciliary body mesectodermal leiomyoma with rapid growth and loss of vision necessitating enucleation. (December 2020) - Alkatan, Hind M.; Al-Dahmash, Saad A.; Aljaedi, Hamad
Abstract: Introduction: Mesectodermal leiomyoma of the ciliary body is a benign rare tumor that rarely presents acutely with a complicated clinical course. Presentation of case: We are reporting a 39-year-old healthy female who presented with subacute blurred vision in her right eye secondary to a ciliary body mass. Initial fine needle aspiration biopsy ruled out a melanoma but the patient meanwhile experienced rapid complicated growth of the mass with vision loss, for which her right globe was eventually enucleated. The tumor was diagnosed histopathologically to be mesectodermal leiomyoma. Discussion: The clinical course of our case was unique because of the subacute onset of her symptoms, the rapid growth of her benign tumor, and the complicated tumor behaviour leading to enucleation. An acute presentation of mesectodermal leiomyoma has been reported only once among similar cases in the recent literature. The tumor in our case showed the characteristic histopathological and immunohistochemical findings described before. Conclusion: Ophthalmologists should be aware of the unusual acute/subacute presentation of a rather benign lesion. Delayed diagnosis may result in ophthalmic complications and loss of the globe. Highlights: Ciliary body mesectodermal leiomyoma is a benign tumor that rarely presents acutely. We present this tumor in a patient with rapid growth and lost vision resulting in enucleation. Histopathological diagnosis may be challenging and needs immunohistochemical stains. Early detection allows simple excision and globe salvage.